Membangun Loyalitas Pelanggan: Peran Kepuasan dalam Menghubungkan Kualitas Produk dan Promosi - Yuliati, Rosa; Hidayati, Nur; Asiyah, Siti (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This study aims to determine the direct and mediating effects between product quality and promotion on customer satisfaction and customer loyalty in the Kattoen brand. Methods: This research uses a non-probability sampling method. Finding: The results showed that product quality and promotion had no significant effect on customer loyalty, customer satisfaction had a significant effect on customer loyalty, product quality had no significant effect on customer satisfaction, and promotion had a significant effect on customer satisfaction. Customer satisfaction does not mediate the influence between product quality on customer loyalty, customer satisfaction mediates the influence between promotions on customer loyalty. Theoretical contribution/Originality: This research proves that promotional activities on social media are very effective. Practitioner/Policy implication: Customer satisfaction is proven to be able to increase customer loyalty, to create customer loyalty, the company must improve product quality and promotional strategies properly. Research limitation: The research was only conducted in Malang City